D-Branes and M-Theory in Supersting Theories - Freddy P Zen; Jusak S Kosasih (Institut Teknologi Bandung, 2003)
D-Branes in (type IIA and IIB) superstring theories are investigated in spacetime of dimension d = 10. Type IIA and IIB superstrings are derived using GSO (Gliozzi, Scherk, Olive) projection on Ramond-Ramond (RR) sector. The degrees of freedom in that theory contains extended stable objects D-branes with eld strengths F(1); F(3); F(5) for type IIB and F(2); F(4) for type IIA, in addition to graviton, dilaton and antisymmetric tensor of rank 2. From the T-duality for open strings, we also show the existence of D-branes from the Dirichlet boundary conditions. At the end we review the dualities that relate all ve of the 10 dimensional superstring theories and a quantum extension of 11 dimensional supergravity called M theory as well as the recently found correspondence between string theory and gauge theory, the AdS/CFT conjecture.